Câu $81$:
$$4f(x) + 5f\left(\dfrac{1}{x}\right) + 9x = 0 \, (1)$$
Thay $x$ bằng $\dfrac{1}{x}$ vào $(1)$ ta được:
$$4f\left(\dfrac{1}{x}\right) + 5f(x) + \dfrac{9}{x} = 0 \, (2)$$
Cộng $(1)$ và $(2)$ ta được:
$$9f(x) + 9f\left(\dfrac{1}{x}\right) + 9\left(x + \dfrac{1}{x}\right) = 0$$
$$\implies f(x) + f\left(\dfrac{1}{x}\right) = -x - \dfrac{1}{x}$$
Xét lại $(2)$:
$$4f\left(\dfrac{1}{x}\right) + 5f(x) + \dfrac{9}{x} = 0$$
$$\implies 4\left(f\left(\dfrac{1}{x}\right) + f(x)\right) + f(x) + \dfrac{9}{x} = 0$$
$$\implies f(x) = 4x - \dfrac{5}{x}$$
Thay vào giới hạn và sử dụng lượng liên hợp để tìm ra lim.
Đáp án: D
Câu 83:
Đặt $g(x) = \sqrt[2017]{f(x) + 1}$. Khi đó: $g(0) = \sqrt[2017]{f(0) + 1} = 1$
Ta có:
$$\lim_{x \to 0} \dfrac{\sqrt[2017]{f(x) + 1} - 1}{x} = \lim_{x \to 0} \dfrac{g(x) - 1}{x}$$
$$= \lim_{x \to 0} \dfrac{(g(x) - 1)(g^{2016}(x) + g^{2015}(x) + \cdots + g(x) + 1)}{x(g^{2016}(x) + g^{2015}(x) + \cdots + g(x) + 1)}$$
$$= \lim_{x \to 0} \dfrac{g^{2017}(x) - 1}{x(g^{2016}(x) + g^{2015}(x) + \cdots + g(x) + 1)}$$
$$= \lim_{x \to 0} \dfrac{f(x)}{x(g^{2016}(x) + g^{2015}(x) + \cdots + g(x) + 1)}$$
$$= \lim_{x \to 0} \dfrac{x + 2x^2 + 3x^3 + \cdots + 2017x^{2017}}{x(g^{2016}(x) + g^{2015}(x) + \cdots + g(x) + 1)}$$
$$= \lim_{x \to 0} \dfrac{1 + 2x + 3x^2 + \cdots + 2017x^{2016}}{g^{2016}(x) + g^{2015}(x) + \cdots + g(x) + 1}$$
$$= \dfrac{1}{1 + 1 + \cdots + 1 + 1} \text{ ($2017$ số $1$ ở mẫu) }$$
$$= \dfrac{1}{2017}$$
Đáp án: A